Teacher Identities in the Digital Age: A Cross-Provincial Analysis of Social Media Guidance for Educators - Porter, Gemma (Journal of Contemporary Issues in Education, 2024)
This paper examines employer policies and professional organization guidelines governing teacher use of social media across four Canadian provinces: New Brunswick, Ontario, Saskatchewan, and British Columbia. Findings indicate that current policies and guidance often overlook the nuanced role social media plays in shaping teacher identities, focusing instead on risk management and narrow definitions of professionalism. This study advocates for policies that better reflect the complexities of teacher identity formation within digital spaces, highlighting the need for supportive guidance that empowers educators in their online interactions. By addressing this gap, the study lays a foundation for future research and offers practical implications for teachers, employers, and policymakers committed to fostering constructive digital engagement and teacher identity development.